Communitas: da preponderância da coletividade na teologia do culto de João Calvino - Mota, Agnaldo dos Santos (2014)
This dissertation presents a study of the theology of worship proposed by John Calvin, seeking to highlight the aspects that foster the preponderance of the community as opposed to the individuality seen in contemporary worship, and, whenever possible, pointing out the reasons why the Reformer excelled in the emphasis of the collective. The research moves between two fields of knowledge, Religious Studies and Theology. The text, in principle, focuses on the Religious Reformed Movement of the sixteenth century, describing the synthesis in Calvin s thought, especially his understanding of worship. We also make an examination of the evolution, or modification, of Calvin's theology of worship, particularly in England, Scotland and the USA, together with a comparative analysis of the Genevan Calvinist Worship and Puritan Worship, showing that the second, with its individualistic theological nuances, modified the first, and thus significantly gave special contribution to individualism seen in the liturgy of the contemporary Calvinist worship, and influenced in building the social imaginary of the followers of this branch of Calvinism and its heirs.